PAX6 is frequently expressed in ependymal tumours and associated with prognostic relevant subgroups. Issue 11 (28th June 2021) - Tabasaran, Julian; Schuhmann, Martin; Ebinger, Martin; Honegger, Jürgen; Renovanz, Mirjam; Schittenhelm, Jens
Abstract : Aims: An ependymoma shows divergent morphological and molecular features depending on their location. The paired box 6 ( PAX6 ) transcription factor is a putative tumour suppressor and drives cancer cells towards a stem cell-like state. A transcriptome study reported high PAX6 expression in ependymal tumours, but data on protein expression are lacking. Methods: We, therefore, analysed PAX6 expression by immunohistochemistry in 172 ependymoma samples and correlated its expression to histology, WHO grade, anatomical location and molecular subgroups. Results: Mean PAX6 nuclear expression in ependymoma was 27.5% (95% CI 23.3 to 31.7). PAX6 expression in subependymoma (mean: 5%) was significantly lower compared with myxopapillary (30%), WHO grade II (26%) and anaplastic ependymoma (35%). Supratentorial ependymomas also displayed significant lower PAX6 levels (15%) compared with spinal cord tumours (30%). Expression levels in YAP1-fused ependymoma (41%) were higher compared with REL-associated protein (RELA)-fusion positive tumours (17%), while PAX6 expression was similar in posterior fossa group A (33%) and B (29%) ependymomas. Kaplan-Meier analysis in RELA-fusion positive ependymomas and posterior fossa group B showed a significant better outcome for PAX6 at or above the cut-off of 19.45% compared with tumours with PAX6 below the cut-off. Conclusions: We demonstrate that PAX6 is frequently expressed in human ependymal tumours and immunohistochemistry may be helpful in determining prognostic relevant subgroups.